Framing â€œTong Ngin Fan Ngin Jit Jongâ€ Slogan as Construction of Three Online Media Framing at Bangka - Sya, Meta; Marta, Rustono Farady (Jurnal Studi Komunikasi, 2019)
This research discusses about frame of online newspaper that convey the slogan of Tong Ngin Fan Ngin Jit Jong. The slogan itself reflects the equality slogan for both Malay and Chinese ethnics in Bangka Belitung Islands Province. The deliverance of this issue departs from the framing differences of the "Tong Ngin Fan Ngin Jit Jong" slogan by several online newspapers. This study aimed to investigate the framing of issues raised in three perspectives by online newspapers, such as m.radarbangka.co.id, bangka.tribunnews.com, and mediaindonesia.com. This research utilises the framing method by Fairhurst and Sarr. The research discovers framing similarities and differences of those three online newspaper. This research also discovers media perspective that leans towards a political figure mentioned in the news content.